1985
DOI: 10.1083/jcb.101.4.1371
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of tau in the mammalian central nervous system.

Abstract: We have determined the biochemical and immunocytochemical localization of the heterogeneous microtubule-associated protein tau using a monoclonal antibody that binds to all of the tau polypeptides in both bovine and rat brain. Using immunoblot assays and competitive enzyme-linked immunosorbent assays, we have shown tau to be more abundant in bovine white matter extracts and microtubules than in extracts and microtubules from an enriched gray matter region of the brain. On a per mole basis, twice-cycled microtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
908
5
4

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,467 publications
(954 citation statements)
references
References 45 publications
24
908
5
4
Order By: Relevance
“…In the sham-operated rats, the pattern of T-l im munoreactivity was consistent with the axonal lo calization described previously (Binder et al, 1985). The neuropil was intensely stained and neu ronal perikarya and dendrites were immunonega tive.…”
Section: -1supporting
confidence: 88%
“…In the sham-operated rats, the pattern of T-l im munoreactivity was consistent with the axonal lo calization described previously (Binder et al, 1985). The neuropil was intensely stained and neu ronal perikarya and dendrites were immunonega tive.…”
Section: -1supporting
confidence: 88%
“…Tau, which is preferentially found in axons (Binder et al, 1985), and MAP2, which is preferentially found in dendrites (Bernhardt and Matus, 1984), might bundle MTs because overexpression of these proteins in insect cells generates processes that have MT-MT spacings that reflect the size of the MAP (Chen et al, 1992). Nonetheless, mice lacking either tau or MAP2 have relatively normal neurons, which suggests that other factors are involved (Harada et al, 1994;Teng et al, 2001).…”
Section: Mt Bundlingmentioning
confidence: 98%
“…1,2 The synthesis of tau is upregulated along with tubulin during neuronal differentiation; in mature neurons, tau occurs mostly in the axon and is largely excluded from the somatodendritic compartment, whereas other MAPs (e.g., MAP2) predominate in dendrites. 3,4 Microtubules must be able to dynamically grow and shrink, to support cellular shape changes. This is a prerequisite to establishing neuronal polarity and axonal outgrowth.…”
Section: Cell Biology and Function Of Taumentioning
confidence: 99%